The Effect of Brainstorming Strategy on Learning Some Fundamental Skill in Basketball Players Of Sulaymaniyah Sport School Club - Abdulla, Razan Hassan; Saeed, Vian Abdulkareem (Journal of Physical Education, 2021)
The researcher aimed at identifying the effect of barnstorming strategy on basketball fundamental skill for Sulaymaniyah sport school club. The researchers used the experimental method on (10) basketball players from Sulaymania sport school club. The program was applied for six weeks with two sessions per week to conclude the positive effect of the teaching program using brainstorming on offensive skills in basketball players. The researchers also concluded that the teaching program was very useful for developing the subjects’ abilities and needs. Finally, they recommended using this style for teaching physical education and sport sciences students as well as using this style for teaching other skills in other sports due to its great positive effect.